Prior use of therapeutic anticoagulation does not protect against COVID‐19 related clinical outcomes in hospitalized patients: A propensity score‐matched cohort study. Issue 12 (7th May 2021) - Spiegelenberg, Janneke P.; van Gelder, Marleen M. H. J.; Maas, Martje L.; Hovens, Marcel M. C.; Esselink, Anne; Dofferhoff, Anton S. M.; Janssen, Rob; van de Maat, Josephine; Janssen, Nico; Blaauw, Marc; Hassing, Robert‐Jan; van Apeldoorn, Marjan; et al.
Abstract : The hypercoagulable state observed in COVID‐19 could be responsible for morbidity and mortality. In this retrospective study we investigated whether therapeutic anticoagulation prior to infection has a beneficial effect in hospitalized COVID‐19 patients. This study included 1154 COVID‐19 patients admitted to 6 hospitals in the Netherlands between March and May 2020. We applied 1:3 propensity score matching to evaluate the association between prior therapeutic anticoagulation use and clinical outcome, with in hospital mortality as primary endpoint. In total, 190 (16%) patients used therapeutic anticoagulation prior to admission. In the propensity score matched analyses, we observed no associations between prior use of therapeutic anticoagulation and overall mortality (risk ratio 1.02 [95% confidence interval; 0.80–1.30]) or length of hospital stay (7.0 [4–12] vs . 7.0 [4–12] days, P = .69), although we observed a lower risk of pulmonary embolism (0.19 [0.05–0.80]). This study shows that prior use of therapeutic anticoagulation is not associated with improved clinical outcome in hospitalized COVID‐19 patients.